Time-dependent changes in striatal monoamine levels and gene expression following single and repeated amphetamine administration in rats - Sequeira Cordero, Andrey (2021)
As drug addiction may result from pathological usurpations of learning and memory’s neural mechanisms, we focused on the amphetamine-induced time-dependent neurochemical changes associated with neural plasticity. We used juvenile rats as the risk for drug abuse is higher during adolescence. Experiment 1 served to define the appropriate amphetamine dose and the neurochemical effects of a single administration. In experiment 2, rats received seven amphetamine or saline injections in the open-field test throughout a twelve-day period. We measured the mRNA levels of the brain-derived neurotrophic factor (BDNF), its tropomyosin receptor kinase B (TrkB), the cAMP response element-binding protein (CREB), the microRNA-132, the Rho GTPase-activating protein 32 (p250GAP), the corticotropin-releasing factor (CRF), and monoamines and amino-acids contents in the nucleus accumbens and the dorsal striatum 45, 90, and 180 min after the last injection. We found that amphetamine changed gene expression only at certain time points and in a dose and region-dependent manner. Repeated but not single administrations upregulated accumbal and striatal BDNF (180 min) and striatal pri-miR- 132 (90 min) expression, while downregulated accumbal CREB levels (90 min). As only some drug users develop addiction, we compared brain parameters between low and high amphetamine responders. Prone subjects characterized by having reduced striatal 5-HT metabolism, higher accumbal BDNF and TrkB expression, and lower levels of CREB in the dorsal striatum and p250GAP in both regions. Thus, individual differences in druginduced changes in neurotransmission and gene expression in nigrostriatal and mesolimbic dopaminergic pathways may underlie the plasticity adaptations associated with behavioral sensitization to amphetamine.